2022
DOI: 10.1007/s11150-022-09604-y
|View full text |Cite
|
Sign up to set email alerts
|

Child penalty in Russia: evidence from an event study

Abstract: In this paper, we investigate the child penalty in Russia using data from the Russian Longitudinal Monitoring Survey (RLMS) and the methodological framework of event studies. We find that five years after childbirth, women suffer an earnings penalty, while no effect is observed for men. The mothers’ penalty stems exclusively from lower employment after childbirth. Contrary to similar studies on Western Europe and the US, we do not find penalties in terms of working hours or hourly wage rates for women who rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 81 publications
1
3
0
Order By: Relevance
“…In some aspects the case of Serbia fits well with other results available for postcommunist countries (Cukrowska-Torzewska and Matysiak, 2020; Lebedinski et al, 2020). The lack of the part-time options and low employment flexibility typically means that after an initial period of taking care of infants (children aged 0-2 years) women in Serbia return to the work they previously had, with the same working hours and wage rates.…”
Section: Parenthood and Labour Market Outcomes In Serbiasupporting
confidence: 82%
See 1 more Smart Citation
“…In some aspects the case of Serbia fits well with other results available for postcommunist countries (Cukrowska-Torzewska and Matysiak, 2020; Lebedinski et al, 2020). The lack of the part-time options and low employment flexibility typically means that after an initial period of taking care of infants (children aged 0-2 years) women in Serbia return to the work they previously had, with the same working hours and wage rates.…”
Section: Parenthood and Labour Market Outcomes In Serbiasupporting
confidence: 82%
“…Other evidence on post-socialist countries suggests that after childbirth women in Russia initially experience strong employment penalties (a reduction in employment levels of between 40 and 65 percentage points), and while these penalties are lasting they stabilise at about 6% after five years (Lebedinski et al, 2020). The same study finds no penalties in terms of working hours or hourly wages.…”
Section: Literature Reviewmentioning
confidence: 88%
“…The mothers' penalty stems exclusively from lower employment after childbirth; the authors do not find penalties in terms of working hours or hourly wage rates for women who remain in the labour force. The study also finds that parenthood decreases the probability of working in supervisory positions for mothers (Lebedinski et al, 2022). To the extent that the flagship programmes increase numbers of births, or move childbirth to an earlier point in the mother's work life, available evidence thus suggests that they hinder employment.…”
Section: Parental Leavementioning
confidence: 86%
“…Evidence from Russia indicates that the effect of childbirth on mothers' employment generally is negative. A recent study by Lebedinski et al (2022) found that five years after childbirth, women suffer an earnings penalty, while no effect is observed for men. The mothers' penalty stems exclusively from lower employment after childbirth; the authors do not find penalties in terms of working hours or hourly wage rates for women who remain in the labour force.…”
Section: Parental Leavementioning
confidence: 98%